Accurate and rapid analysis of residual disease in patients with CML using specific fluorescent hybridization probes for real time quantitative RT-PCR - Emig, Michael; Saußele, Susanne; Wittor, Heiko; Weißer, Andreas; Reiter, Andreas; Willer, Andreas; Berger, Ute; Hehlmann, Rüdiger; Cross, Nicholas C. P.; Hochhaus, Andreas (Leukemia, 1999)
We sought to establish a rapid and reliable RT-PCR approach for detection and quantification of BCR-ABL fusion transcripts using the LightCycler technology. This device combines rapid thermocycling with online detection of PCR product formation and is based on the fluorescence resonance energy transfer (FRET) between two adjacent hybridization probes carrying donor and acceptor fluorophores. A pair of probes was designed that was complementary to ABL exon 3, thus enabling detection of all known BCR-ABL variants and also normal ABL as an internal control. Conditions were established to amplify less than 10 target molecules/reaction and to detect one CML cell in 105cells from healthy donors. To determine the utility of the assay, we quantified BCR-ABL and ABL transcripts in 254 samples (222 peripheral blood, 32 bone marrow) from 120 patients with CML after therapy with IFN-α (n = 219), allogeneic BMT (n = 17), chemotherapy (n = 11), or at diagnosis (n = 7). The level of residual disease in the 245 BCR-ABL positive specimens was expressed as the ratio of BCR-ABL/ABL. This ratio was compared to results obtained by three established methods from contemporaneous specimens. A highly significant correlation was seen between the BCR-ABL/ABL ratios determined by the LightCycler and (1) the BCR-ABL/ABL ratios obtained by nested competitive RT-PCR (n = 201, r = 0.90, P < 0.0001); (2) the proportion of philadelphia chromosome positive metaphases determined by cytogenetics (n = 81, P < 0.0001); and (3) the bcr ratio determined by southern blot analysis (n = 122, P < 0.0001). we conclude that real-time pcr with hybridization probes is a reliable and sensitive method to monitor cml patients after therapy. the major advantages of the methodology are (1) amplification and product analysis are performed in the same reaction vessel, avoiding the risk of contamination; (2) the results are standardized by the quantification of housekeeping genes; and (3) the complete pcr analysis takes less than 60 min.